Множинність читацьких інтерпретацій художньої умовності як наратив- на стратегія тексту - Вещикова, Олена Сергіївна; Veshchykova, O. S. (My University, 2014)
Пропонована стаття являє собою спробу аналізу художнього тексту з точки зору розгортання наративних стратегій. Розглядаються наукові концепції поняття «наративна стратегія» вітчизняних та зарубіжних літературознавців. Надається власна дефініція терміна «наративна стратегія». На матеріалі роману Г. Пагутяк «Сни Юлії і Германа» досліджується експлікація наративної стратегії, яка створює варіативність рецепції читачем онейротопів, можливість самостійно обирати форму умовності, котра визначає текст. This paper is an attempt to analyze a text of fiction from the point of view of the deployment of narrative strategies. We consider scientific concepts of the term «narrative strategy» by Ukrainian and foreign literary critics. We give our own definition of the term «narrative strategy». Explication of narrative strategies is studied in H. Pahutyak’s novel «Dreams of Julia and Herman». This strategy creates the variability of reader’s reception of oneirotopos, the opportunity to choose on one’s own the form of convention that defines the text.
The multiplicity of readers’ interpretations of fictional convention as a narrative strategy of the text
Keywords: наративна стратегія; онейротоп; художня умовність; читацька рецепція; narrative strategy; oneirotopos; fictional convention; reader’s reception